Emotional Experience On E Wom Swiss Bell Silae Hotel In Palu City, Central Sulawesi - Idham, Idham; Yasin, Mohamad; Bin Muhtar, Dzulkifli; Wahab, Abdul (Publisher Cv. Inara, 2024)
Service Quality (SQ), Customer Satisfaction (CS), and Positive Emotional Experience (PEE) have the effect of increasing the positive eWOM of hotel visits. Positive eWOM is a review of the experience felt by consumers who have had a good experience after staying at a hotel. The aim of the research is to test whether Service Quality, Customer Satisfaction (CS), and Positive Emotional Experience, have an influence on increasing positive eWOM visits to Swiss Bel Hotel Silae Palu, based on the Traveloka hotel reservation application site. The aim of the research is the influence of customer satisfaction on eWOM Swiss Bel Hotel Silae Palu. identify the influence of service quality on eWOM of Swiss Bel Hotel Silae Palu. What is the influence of positive emotional experience on eWOM Swiss Bel Hotel Silae Palu. Service quality is important for companies facing competition in the market, satisfying consumer needs and desires, paying attention to service quality (Maulana, 2016). Using quantitative uses numerical measurements. The influence of the Independent Variable on the Dependent Variable is concluded, Customer Satisfaction of the Swiss Bell Silae Hotel in Palu City, has a significant influence on the eWOM of the Swiss Bell Silae Hotel in Palu City. Service Quality provided by the Swiss Bell Silae Hotel in Palu City has a significant influence on the eWOM of the Swiss Bell Silae Hotel in Palu City, Positive Emotional Experience of Swiss Bell Silae Hotel customers in Palu City has a significant influence on Customer Satisfaction of the Swiss Bell Silae Hotel in Palu City. Positive Emotional Experience of Swiss Bell Silae Hotel customers in Palu City has a significant influence on the eWOM of Swiss Bell Silae Hotel in Palu City.